Physicians' Perspective on Prescribing Patterns and Knowledge on Antimicrobial Use and Resistance in Penang, Malaysia: A Qualitative Study - Akhtar, Ali; Khan, Amer Hayat; Zainal, Hadzliana; Ahmad Hassali, Mohamed Azmi; Ali, Irfhan; Ming, Long Chiau (Frontiers in Public Health, 2020)
Background Unnecessary antimicrobial use is an emerging problem throughout the world. To design future interventions to ensure rational antimicrobial use and decrease the risk of antimicrobial resistance, physician’s knowledge and prescribing practices of antimicrobials should be assessed. Therefore, the main objective of this study is to investigate the physician’s knowledge along with their prescribing patterns of antimicrobials in their health care system. Methods The present qualitative study was conducted in a tertiary care public hospital located at Penang island, situated in Northwest of Malaysia. A total of 12 semi-structured, face to face interviews were conducted with purposive sampling technique. Physicians recruited had different specialties. All interviews were audio recorded, then transcribed into English language and analyze by thematic content analysis. Results Four major themes were identified: (1) prescribing patterns of physicians regarding antimicrobials; (2) physician’s knowledge about antimicrobials; (3) antimicrobial resistance; (4) satisfaction with management of infections. Physicians believed in regular educational activities and updates about the latest antimicrobial guidelines may change the prescribing behavior of physicians to optimize the use of antimicrobials. This may lead to decrease in burden of antimicrobial resistance in their health care system. Physicians emphasized that stricter rules and regular monitoring of antimicrobial use should be implemented to overcome the main challenges of antimicrobial resistance. Conclusion Different factors were identified to assist optimized use of antimicrobials and decrease the risk of antimicrobial resistance. The present study helps to design targeted future interventions to ensure rational antimicrobial use and decrease the impact of antimicrobial resistance in Malaysia.